Importance of Indigenous Breeds of Chicken for Rural Economy and Their Improvements for Higher Production Performance - Mahendra Kumar Padhi (Scientifica)
Indigenous/native breeds of chickens are playing an important role in rural economies in most of the developing and underdeveloped countries. They play a major role for the rural poor and marginalised section of the people with respect to their subsidiary income and also provide them with nutritious chicken egg and meat for their own consumption. Performance of native fowl can be improved by change in husbandry, feeding, and better health cover. However, genetic improvement may be made either through selection and crossbreeding or by utilisation of both selection and crossbreeding. Improvement through selection may be time consuming but the improvement will be permanent. Through crossbreeding improvement may be faster but research has to aim for the production of native-type birds with higher production potential. In the present review efforts have been made to present the importance of native fowl to rural economy and their improvement for higher production performance.